Optimization Model Schedule Nervousness in Flight Catering Industry - Aditya Putra Rahardjo (IPTEK Journal of Proceedings Series, 2020)
Abstract―Instability often occurs in production planning, which is also known as schedule nervousness. This phenomenon triggers companies to make various efforts in minimizing the level of instability. In this study, the author tries to look at the schedule nervousness problems of the aviation catering industry in determining the amount of production planning to increase profits. In the context of schedule nervousness, there is a very high difference between the value of the temporary demand which is known 10 hours before with the fix order when the airline has closed the check-in process. This phenomenon makes the aviation catering company must bear the loss in value of the difference in demand that occurs. In one month the company must bear the loss of at least 500 packs of food. Based on those problems, the author tries to make an optimization model with linear programming by determining the number of orders for each airline and class of passengers at a certain service level to produce minimal inventory with large profits. The completion of the model using Lingo software is running well and has produced an optimal solution. The potential cost reduction carried out in the first week of January 2020, has provided the best scenario with the potential for cost savings of the production process around the production cost of around Rp 53 million or about 23%.